PROSEDUR PENENTUAN PRIORITAS PEMELIHARAAN GEDUNG SEKOLAH MENENGAH ATAS NEGERI DI KABUPATEN BALANGAN - Bambang Mulyadi (Jurnal Teknologi Berkelanjutan, 2019)
School buildings have a very important function in the development and growth of education in an area in an effort to realize equitable educational development. Hence, school buildings are infrastructures that need to be managed properly. But according to their characteristics, the quality of school buildings always tends to decrease which is indicated by physical damage in the buildings. Due to funding constraints faced by the Government of Balangan Regency, as well as the many requests for the construction or rehabilitation of state high school buildings from every one fiscal year, the research method needed is Analytical Hierarchy Process (AHP). The object of the study was all public high school buildings in Balangan Regency which were sourced from the Balangan Regency Regional Budget. Secondary data obtained from the Office of Education and the head of senior high school / district vocational. Balangan, Primary data were obtained from distributing questionnaires to 22 respondents, namely the 19th Regional Budget Revenue and Expenditure Team (TAPD) and 3 related Agencies of respondents. The results of the study have been made Priority Building Procedures for School Buildings consisting of stages namely Primary Data Collection, Distribution of Questionnaire Phase I, Determination of Criteria, Preparation of PBS Hierarchy Procedures, Distribution of Questionnaire Phase II and Weighting of Importance of Criteria.